Electrocardiographic Effects of Propofol versus Etomidate in Patients with Brugada Syndrome. (March 2020) - Flamée, Panagiotis; Varnavas, Varnavas; Dewals, Wendy; Carvalho, Hugo; Cools, Wilfried; Bhutia, Jigme Tshering; Beckers, Stefan; Umbrain, Vincent; Verborgh, Christian; Forget, Patrice; Chierchia, Gian-Battista; Brugada, Pedro; et al.
Abstract : Background: Brugada Syndrome is an inherited arrhythmogenic disease, characterized by the typical coved type ST-segment elevation in the right precordial leads from V1 through V3 . The BrugadaDrugs.org Advisory Board recommends avoiding administration of propofol in patients with Brugada Syndrome. Since prospective studies are lacking, it was the purpose of this study to assess the electrocardiographic effects of propofol and etomidate on the ST- and QRS-segments. In this trial, it was hypothesized that administration of propofol or etomidate in bolus for induction of anesthesia, in patients with Brugada Syndrome, do not clinically affect the ST- and QRS-segments and do not induce arrhythmias. Methods: In this prospective, double-blinded trial, 98 patients with established Brugada syndrome were randomized to receive propofol (2 to 3 mg/kg -1 ) or etomidate (0.2 to 0.3 mg/kg -1 ) for induction of anesthesia. The primary endpoints were the changes of the ST- and QRS-segment, and the occurrence of new arrhythmias upon induction of anesthesia. Results: The analysis included 80 patients: 43 were administered propofol and 37 etomidate. None of the patients had a ST elevation greater than or equal to 0.2 mV, one in each group had a ST elevation of 0.15 mV. An ST depression up to −0.15mV was observed eleven times with propofol and five with etomidate. A QRS-prolongation of 25% upon induction was seen in one patient with propofol and three with etomidate. This trial failed to establish any evidence to suggest that changes in either group differed, with most percentiles being zero (median [25th, 75th], 0 [0, 0] vs . 0 [0, 0]). Finally, no new arrhythmias occurred perioperatively in both groups. Conclusions: In this trial, there does not appear to be a significant difference in electrocardiographic changes in patients with Brugada syndrome when propofol versus etomidate were administered for induction of anesthesia. This study did not investigate electrocardiographic changes related to propofol used as an infusion for maintenance of anesthesia, so future studies would be warranted before conclusions about safety of propofol infusions in patients with Brugada syndrome can be determined. Abstract : This study was a prospective randomized double-blind trial that compared groups receiving propofol (n = 43) versus etomidate (n = 37) for induction of general anesthesia. No significant difference in electrocardiographic changes was observed between these two groups.